Representations of Gender Violence in Current Latin American Cultural Creations (Anclajes, 2020)
The articles in this issue focus on the ways in which gender violence impacts its own contexts and communities materially, symbolically, and subjectively. The texts address femicides-feminicides, the exploitation and racialization of bodies within the framework of “gore capitalism” as understood by Sayak Valencia, as well as the violence inflicted on bodies within the border-related contexts of migration and deportation.
Keywords: gender violence; feminicide; masculinities; migration; Latin American studies